A multifunctional paper-based supercapacitor with excellent temperature adaptability, plasticity, tensile strength, self-healing, and high thermoelectric effects. Issue 9 (14th February 2023) - Xiong, Chuanyin; Yang, Qi; Dang, Weihua; Zhou, Qiusheng; Jiang, Xue; Sun, Xuhui; Wang, Zequn; An, Meng; Ni, Yonghao
Abstract : In recent years, the development of multi-functional supercapacitors with high flexibility and strong environmental adaptability has gradually become a focus of attention. Abstract : In recent years, the development of multi-functional supercapacitors with high flexibility and strong environmental adaptability has gradually become a focus of attention. In this work, a multi-functional paper-based supercapacitor with excellent temperature adaptability, plasticity, tensile strength, strong adhesion, and self-healing properties is obtained by introducing PVA and ZnCl2 into carbonized paper-based materials (APC-PVA@ZnCl2 ). The as-obtained APC-PVA@ZnCl2 supercapacitor has excellent adaptability to the environment, even in a low-temperature environment below zero, still maintaining a high volumetric specific capacitance of 3438.45 mF cm −3 and high volumetric specific energy density of 44 mW h cm −3 . Moreover, the APC-PVA@ZnCl2 supercapacitor can be stretched beyond 2400–2500% strain, indicating good tensile properties. In addition, the APC-PVA@ZnCl2 composite can also be used as a sensing material to detect current signals with different characteristics generated by the movement of different parts of the human body, showing excellent sensing performance. Besides, the APC-PVA@ZnCl2 composite also displays outstanding thermoelectric properties. It is hoped that this work can provide a reference for the development of green multi-functional supercapacitors.